3D graphene/δ-MnO2 aerogels for highly efficient and reversible removal of heavy metal ions. Issue 5 (18th January 2016) - Liu, Juntao; Ge, Xiao; Ye, Xinxin; Wang, Guozhong; Zhang, Haimin; Zhou, Hongjian; Zhang, Yunxia; Zhao, Huijun
Abstract : 3D graphene/δ-MnO2 aerogels demonstrated high removal efficiency, fast adsorption kinetics, excellent regeneration towards heavy metal ions based on the perfect integration of surface adsorption and in-depth bulk uptake. Abstract : Novel three-dimensional (3D) graphene/δ-MnO2 aerogels were fabricated via self-assembly and reduction of graphene oxide, followed by in situ solution-phase deposition of ultrathin δ-MnO2 nanosheets. The resultant graphene/δ-MnO2 architectures showed an interconnected 3D network microstructure, in which a large number of ultrathin birnessite MnO2 nanosheets were homogenously deposited on the graphene framework. Due to their unique structural characteristics, the resulting 3D aerogels exhibited a fast adsorption kinetic rate and superior adsorption capacity toward heavy metal ions. The saturated adsorption capacities of graphene/δ-MnO2 aerogels were as large as 643.62 mg g −1 for Pb 2+, 250.31 mg g −1 for Cd 2+ and 228.46 mg g −1 for Cu 2+ calculated by the Langmuir isotherm model, exceeding largely the corresponding pristine 3D graphene and δ-MnO2 nanosheets. It was noted that the heavy metal ions could not only adsorb on the surface of graphene/δ-MnO2, but also intercalate into the interlayer gaps of birnessite MnO2, which reveals the synergistic effect of the static electrical attraction, surface complexation and ion exchange between heavy metal ions and pre-intercalated K +, supported by the expansion of the basic crystal structure of layered MnO2 after adsorption. Furthermore, it is interesting that the regenerated aerogels after the initial HCl and subsequent KOH treatment still maintain their original shape and can be repeatedly used for more than eight cycles without obvious degradation of performance, which achieved the sustainability of the absorbents. More importantly, the hybrid aerogels can be easily separated and do not generate secondary contaminants. High removal efficiency, fast adsorption kinetics, excellent regeneration and reusability, and ease of separation operation make these hybrid aerogels ideal candidates for heavy metal ion decontamination in practical application.